2019
DOI: 10.1111/1467-8454.12167
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sanitation, safe drinking water and health expenditure on infant mortality rate in developing economies

Abstract: Despite of significant growth in all walks of life, the issue of infant mortality still a major concern in most of the developing economies. The World Development Indicators have reported that 4.45 million infants died across the globe in 2015, meaning that 32 deaths per every 1,000 live births. A number of times, the World Health Organization (WHO) have stressed the significance of sanitation, safe drinking water and healthcare facilities in reducing infant mortality rate, though most developing countries sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…This shows that a 1 percent unit increase in government health spending will reduce under-ve mortality rate by -0.128 if other variables are held constant. The nding is consistent with some previous studies [ 22,4,8,6,11,21]. However, it is at variance with a study involving some high income countries where no signi cant relationship was found between public health spending and child mortality [10].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This shows that a 1 percent unit increase in government health spending will reduce under-ve mortality rate by -0.128 if other variables are held constant. The nding is consistent with some previous studies [ 22,4,8,6,11,21]. However, it is at variance with a study involving some high income countries where no signi cant relationship was found between public health spending and child mortality [10].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, when other variables remain unchanged, a unit increase in domestic private health expenditure will lead to an increase of 0.002 in under-ve mortality rate per time. While the nding is in agreement with a couple of studies conducted in the previous years [4,22], it is however, in contrast to some other studies [26,2]. Moreover, the study found that external health expenditure had a signi cant negative effect on under-ve mortality rate for the period under review.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations